Relatório de estágio supervisionado: modelagem e detalhamento de projetos hidrossanitários - França, Rômulo Mattos (Brasil, 2024)
This report describes the supervised internship carried out at the engineering office of the company Aragão e Teixeira Arquitetura e Engenharia LTDA., from September 23 to November 29, 2024, with a total workload of 180 hours. The goal was to provide practical experience in the development of plumbing projects, using Building Information Modeling (BIM) methodology and Revit software. During this period, the intern was tasked with modeling and detailing systems such as sanitary sewage, cold water, and rainwater, always focusing on compliance with Brazilian technical standards. The application of BIM facilitated the integration of systems efficiently, ensuring greater accuracy and reducing errors in the project. This experience also contributed to the development of practical and technical skills, preparing the professional for the challenges of the job market in the fields of engineering and architecture.